Physicochemical Characteristics of Potato (Solanum tuberosum L.) after Chitosan Coating and Storage at Various Temperature - Mudyantini, Widya; Pramesthi, Vionita Dyah; Suranto, Suranto; Solichatun, Solichatun; Pitoyo, Ari; Suratman, Suratman; Purnama, Purin Candra (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2025)
Potato (Solanum tuberosum L.) plant is widely favored due to its versatility in various processed products, but perishable. This study aimed to determine the effect of chitosan coating and storage at various temperatures on the physiological and chemical characteristics of potato tubers. This research used 2 variables, namely the concentration of chitosan (0, 1, 1.5 and 2%) and storage temperatures of 0, 10 and 25°C. The parameters observed included tuber skin color, weight loss, hardness, the thickness of the chitosan layer and tissue penetration, oxygen levels, water content, starch degradation, reduced sugar content, and sprouting amount. Furthermore, data were analyzed using the Analysis of Variance (ANOVA) test. The results showed the effect of chitosan coating and storage temperature on weight loss, color, oxygen level, hardness, water content, starch degradation, and reduced sugar content in potato tubers during storage. The most effective treatment was 1.5% chitosan coating combined with a storage temperature of 10°C.